Unhealthy parenting strategies: situational (dis-)incentives, Machiavellian personality, and their interaction on misuse of ADHD medication for healthy children - Sattler, Sebastian (Social science research, 2021)
Some parents engage in the potentially unhealthy and morally debateable parenting practice of giving prescription stimulant drugs to healthy children to boost their school and extracurricular performance. However, the parents' underlying reasoning remains unexamined. This web-based study (N Respondents = 1360) simultaneously investigates eight experimentally-varied situational (dis-)incentives (e.g., financial gains and drug properties) within a factorial vignette survey (N Vignettes = 256), Machiavellianism as a measured socially relevant personality trait, and possible interaction effects. Results show that approximately 40% of the described situations (N Evaluations = 5440) provoked some willingness to medicate healthy children. Multilevel mixed-effect models revealed that this willingness was higher, for example, with increasing financial gains and weaker side effects. Machiavellians disclosed a higher willingness. They were more responsive to financial gains and threats (e.g., probable side effects). Respondents’ sex, age, ethnicity, and experience with prescription drugs also had effects. Prevention measures might emphasize the dangers and limited potential of prescription drugs for healthy children.